Identification of SNPs, QTLs, and dominant markers associated with wheat grain flavor using genotyping-by-sequencing. (July 2017) - Kiszonas, Alecia M.; Boehm, Jeffrey D.; See, Deven; Morris, Craig F.
Abstract: Consumer acceptance of whole wheat products can be hindered by the flavor, aroma, and texture. A laboratory mouse model system was used to examine flavor using a two-choice feeding system employing a common check variety and the Student's t statistic as a consumption phenotype. Samples were from a doubled haploid population derived from "Yummy" (Louise) and "yucky" (Yumai34) soft white spring wheat parents. Genotyping-by-sequencing (GBS) identified 655 single nucleotide polymorphic (SNP) markers that differed between the two parents, which were used to create a genetic map with 24 linkage groups. Thirty-nine SNP markers exhibited a significant marker-trait association with consumption, and four significant QTL were detected. Additionally, a novel approach that identified dominant markers successfully found both Louise- and Yumai34-dominant GBS sequence tags. The Louise-dominant markers exhibited high levels of marker-trait association with the Student's t statistic flavor preference phenotype. In total, markers mapped to seven genic regions. In particular, dominant markers on 4DL exhibited the greatest F -values and provided the strongest evidence that genes involved in wheat flavor were located there. This work furthers the understanding of the genetics involved in wheat grain flavor and will aid in the development of varieties with greater consumer acceptance for whole-wheat products. Highlights: Next-generation genotyping-by-sequencing was used to identify genic regions related to flavor of wheat grain. A set of doubled-haploids was analyzed using a mouse model system and innovative phenotype for flavor preference. Major QTL and marker sequences were identified for flavor.